If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3a = 11 + -1a Solving 7 + 3a = 11 + -1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'a' to each side of the equation. 7 + 3a + a = 11 + -1a + a Combine like terms: 3a + a = 4a 7 + 4a = 11 + -1a + a Combine like terms: -1a + a = 0 7 + 4a = 11 + 0 7 + 4a = 11 Add '-7' to each side of the equation. 7 + -7 + 4a = 11 + -7 Combine like terms: 7 + -7 = 0 0 + 4a = 11 + -7 4a = 11 + -7 Combine like terms: 11 + -7 = 4 4a = 4 Divide each side by '4'. a = 1 Simplifying a = 1
| 3(4x-6)=2(4x-3)-(x+8) | | 13.04=f+8.25 | | 9n-3n= | | 13(t+1)-3(2+4t)=48 | | 180=(9x+4)-y | | -15=-5t^2+30t | | 9-3x+5x=-11 | | 2-(x+3)=6 | | 5x+4=37 | | X^2+6x-34=0 | | y+x=y-x | | 2(x-5)+2x=x+3x-2x | | 180+(9x+4)=y | | 20-0.75x+0.55x=10 | | 55+8(25)=x | | 55+8=25 | | -1x^2+4=2x^2-5 | | -20=-10(x+12) | | .40=.5-12 | | 9x-8=9x+6 | | 5x+3(x-4)=8x-12 | | (7)(-6)= | | 12+8x-4=5+2(3x-1) | | 4x+8x+150=164 | | 16(x-2)2-25=0 | | 3(2x+3)=11x+8-5x+1 | | 1x^2+17x+16=0 | | -3-3(8c+7)= | | -8.3x-4.5y+3.4x+3.7y= | | 48=3(2)x | | v-2.9=10.44(46.16568) | | -8=6(x-8) |